Production of flour film from waste flour during noodle production and its application for preservation of fresh strawberries - Rattana Muangrat (2018)
© 2018 The Author(s). The flour film (75% w/v) with 40% w/w plasticizer/waste flour, at 2:1 w/w glycerol:sorbitol and formulated with 20% w/w potassium sorbate/waste flour, was used to cover fresh strawberries on polystyrene foam, and the quality of the fruit was monitored during storage at 5°C and 90% relative humidity for 9 days. The results revealed that the fresh strawberries covered with such film had average phenolic contents, free radical antioxidant activity, and firmness equal to 326.12 mg gallic acid/100 g fresh strawberry and 2.66 mg Trolox/g strawberry, and 0.27 N, respectively. These values were higher than those obtained for the strawberries covered with film having no added potassium sorbate, and the strawberries with no film (control), respectively. Also, among the samples studied, the total plate counts (log CFU/g) of the stored strawberries covered with film, containing 20% w/w potassium sorbate/waste flour, were lower.